Academic spam mails from "Predatory Journals" in cardiology: a cross-sectional study over 3 months. (3rd October 2022) - Ohlow, M
Abstract: Background: Numerous online journals are referred to as predatory journals because their efforts are focused primarily on collecting publication fees rather than on content, peer review, or manuscript presentation. Many of these journals send Academic Spam Mails (ASM), requesting manuscript submissions. Purpose/Methods: Over a 3-month period, all ASMs addressed to the author were collected and analyzed. A fake publication was created with a commonly used structure (Introduction, Methods, Results and Discussion). The article just repeated the phrase "Please get me off your mailing list" over and over again. This publication was submitted in response to each request to test the control mechanisms of the respective journals. Results: During the study period, excluding duplicate requests, 125 ASMs (average 2.1 per business day) were received from a wide variety of journals spanning 38 different subject areas, of which 29/38 (76.4%) were from the medical field. 16/125 (16%) were related to a previously published article but not among the author's most important publications (median h-index rank 22; range 10–138). The majority (73.6%) of journals were listed in Beall's predatory journal list, only an absolute minority (0.8%) were listed in the Directory of Open Access Journals, and 96% were not listed in PubMed. Original papers (94.4%), reviews (88.0%), and case reports (87.2%) were most frequently requested; the publication charge (APC) was a median of $1, 199 (range $50–3, 586); in about 22% of cases, it was not apparent whether APCs were charged and, if so, how much. For the 125 nonsense publications sent out, there was a response in 16/125 (13%) (6 acknowledgements of receipt, 3 apologies, 2 the journal comments that the publication consisted of only one sentence, and 5 other responses). Interestingly, in one case editorial board members had also created a nonsense publication titled: "Ok we not send mail to you" and sent it to the author. 21.6% of the journals had sent ASM to the author again during the next months. Conclusions: Academic spam mails from "predatory" online journals are a common problem. They are recognizable by their appearance in warning lists or non-appearance in directories of reputable open access journals. A placement of a nonsense publication in such a "predatory journal" was not successful. Funding Acknowledgement: Type of funding sources: None.